Nine beautiful things: A self-administered online positive psychology intervention on the beauty in nature, arts, and behaviors increases happiness and ameliorates depressive symptoms. (May 2016) - Proyer, René T.; Gander, Fabian; Wellenzohn, Sara; Ruch, Willibald
Abstract: We tested the effectiveness of a self-administered online positive psychology intervention which addressed the appreciation of beauty and excellence on happiness and depression directly after the intervention, after one week, and one, three, and six months. One hundred thirteen adults were randomly assigned to a "9 beautiful things" intervention (IG; n = 59), or a placebo control group ("early memories"; n = 54). Participants in the IG were asked to write down (a) three beautiful things in human behavior; (b) three things they experienced as beautiful in nature and/or the environment; and (c) three beautiful things related to beauty in general that they observed. Findings show increased levels of happiness in the intervention group at post-test, after one week and one month, and amelioration of depressive symptoms at the post-test and one week after the intervention. The effect sizes were small to medium (η 2  = .03 to .07). Overall, this initial study provides support for the notion that the "9 beautiful things" intervention may be effective in increasing people's well-being—at least in a short term. Highlights: Only few intervention studies on the appreciation of beauty and excellence exist. A randomized placebo-controlled online study was conducted. There were short term effects on happiness and depression.